Analysis of The Marketing Model of Rafting Sports Tourism in Parakan Kondang Sumedang - Darmeswara Rosidin; Indra Safari; Rizal Ahmad Fauzi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This research is motivated by problems in rafting which aims to analyze the marketing model of rafting activities in Parakan Kondang, Sumedang City. This study uses a qualitative method with a case study design. Data collection techniques are interviews and documentation accompanied by data validation in the form of triangulation techniques, and data processing using Nvivo 15 software. The subjects of the study were 3 people including the Disparbudpora, business owners, and part-time students. The results of the Word Frequency Query found during the interview were widely discussed such as rafting sports tourism, promotional media, facilities, and sports tourism packages. Positive implications include, with the analysis of the marketing model for white water rafting sports tourism in Parakan Kondang, white water rafting sports tourism contributes to tourism in the Sumedang area. Based on the researcher’s analysis, this digital marketing model is a marketing model used by rafting sport tourism in Parakan Kondang Sumedang to increase the number of tourists.